Project management model of motor vehicle development with consideration of built-in quality concept requirements - Zhidkikh Nikita; Smolyaninov Andrey; Deniskin Yury; Polity Violetta; Mangushev Ilgiz (E3S Web of Conferences, 2023)
Problem of long timeframes of new car model development cycle due to excessive testing process of numerous vehicle prototypes is specified. Positive example of solving the problem using digital twin, computer modelling and virtual testing technologies in Formula 1 is given. Positive effect of virtual verification and validation during the development process on built-in product quality and development cycle time reduction is indicated. Existing project management V-models in automotive and information technology industries are reviewed and analyzed. State standards and methodologies of project management, lean manufacturing and digital twin development are reviewed. The improvements based on project life cycle, project management processes and product life cycle are enumerated and explained. Improved V-shaped project management model is described and visualized. The proposed model positive effects are described: it allows to increase the level of built-in vehicle quality, shorten its development cycle timeframes while providing the connection between project management and product development processes.